Stereotip Gender Dalam Audit: Analisis Bias Implisit Pada Auditor Perempuan - Resti Astika; Aristanti Widyaningsih; Nelly Nur Apandi (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2025)
The number of female employees has been increasing annually, including in the auditing profession. However, paradoxically, this increase has brought gender issues to the forefront of public attention. This study aims to examine the impact of gender stereotypes and implicit bias on female auditors in the auditing profession. Through a comprehensive literature review sourced from Google Scholar, books, and reputable official websites, this study analyzes various literatures discussing gender stereotypes and implicit bias in the context of the auditing profession. The results of the literature review indicate that gender stereotypes and implicit bias associated with female auditors significantly affect their performance and audit quality. Despite possessing equal competence to male auditors, female auditors often face challenges and discrimination stemming from unconscious negative perceptions. This implicit bias can manifest in various forms, ranging from unfair performance evaluations to limited promotion opportunities. This study concludes that to address this issue, various strategies are needed at the individual, organizational, and systemic levels. Some strategies that can be implemented include raising awareness of implicit bias, building inclusive work environments, and developing policies that support gender equality. In doing so, it is hoped that the negative impacts of gender stereotypes and implicit bias can be reduced, and a more equitable and productive work environment can be created for all auditors.